Briquetting of Palm Kernel Shell - KE Ugwu; KE Agbo (Journal of Applied Sciences and Environmental Management)
In several developing countries, briquettes from agricultural residues contribute significantly to the energy mix especially for small scale and household requirements. In this work, briquettes were produced from Palm kernel shell. This was achieved by carbonising the shell to get the charcoal followed by the pulverization of the charcoal. Starch was used as a binder. The briquettes were analyzed for their combustion characteristics. The results obtained showed that the Palm kernel shell briquettes had higher calorific value than the briquettes from charcoal and sawdust. It also had other desirable combustion characteristics. @JASEM